PSYCHOPATHIC ACTION IN LOVES MUSIC LOVES TO DANCE NOVEL - Eti Kusmala Dewi; Lisa Aprilia (Universitas Muhammadiyah Lampung, 2022)
The writer applied the theories that were relevant and support in this thesis, those are: Psychological approach, theory of psychopath and characteristics of psychopath. Meanwhile, the writer used descriptive qualitative research and library research to make complete this thesis. The data and data source is taken from the novel, Loves Music Loves to Dance by Mary Higgins Clark like: the dialogue, and narration. And the data source required from books, journals, and articles in internet sites related to the topic discussed. Moreover, the analysis is the main point in composing this thesis in order to figure out the action of Charley’s psychopath as a serial killer. The result of the analysis is psychopath has his own view which is very different from a normal person and psychopath usually cannot stop his action until the satisfaction of his own fulfilled.